2020
DOI: 10.1042/cs20201274
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibition versus sulfonylurea treatment effects on electrolyte and acid–base balance: secondary analysis of a clinical trial reaching glycemic equipoise: Tubular effects of SGLT2 inhibition in Type 2 diabetes

Abstract: Sodium–glucose transporter (SGLT)2 inhibitors increase plasma magnesium and plasma phosphate and may cause ketoacidosis, but the contribution of improved glycemic control to these observations as well as effects on other electrolytes and acid–base parameters remain unknown. Therefore, our objective was to compare the effects of SGLT2 inhibitors dapagliflozin and sulfonylurea gliclazide on plasma electrolytes, urinary electrolyte excretion, and acid–base balance in people with Type 2 diabetes (T2D). We assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…Although there is no major sex-specific differences seen in the larger clinical trials of SGLT2 inhibitors, we still find comparability in our predictions of increase in solute excretion with some trials (Sha et al, 2014;Masuda et al, 2020;van Bommel et al, 2020) and not so much with others (Kapur et al, 2013;Cherney et al, 2014;Tanaka et al, 2017;Eickhoff et al, 2019). van Bommel et al (2020) reported a chloride increase of 0.2-2.4 mmol/l in 24 h upon treatment with dapagliflozin. Masuda et al (2020) also reported an increase to 3 mM/Day in urinary chloride compared to 2.3 mM/Day in control after 8 weeks of treatment with ipragliflozin (in rats).…”
Section: Discussionsupporting
confidence: 50%
“…Although there is no major sex-specific differences seen in the larger clinical trials of SGLT2 inhibitors, we still find comparability in our predictions of increase in solute excretion with some trials (Sha et al, 2014;Masuda et al, 2020;van Bommel et al, 2020) and not so much with others (Kapur et al, 2013;Cherney et al, 2014;Tanaka et al, 2017;Eickhoff et al, 2019). van Bommel et al (2020) reported a chloride increase of 0.2-2.4 mmol/l in 24 h upon treatment with dapagliflozin. Masuda et al (2020) also reported an increase to 3 mM/Day in urinary chloride compared to 2.3 mM/Day in control after 8 weeks of treatment with ipragliflozin (in rats).…”
Section: Discussionsupporting
confidence: 50%
“…Our results showed that dapagliflozin upregulated renal magnesium transporters, including claudin-16 and TRPM6/7, resulting in decreased magnesium excretion. It is therefore indicated that both paracellular and transcellular transport were increased [26]. Moreover, the in vitro study by monitoring intracellular magnesium concentration suggested dapagliflozin increased trans-epithelial magnesium transport via TRPM6.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, correcting hypomagnesemia may help glycemic control in diabetes, but not vice versa. 17 The mechanism underlying the renal benefit of SGLT2is is likely to be independent of glucose levels and may possibly stem from a reduction in intra-glomerular pressure 18 and other possible mechanisms presently being studied. 19 SGLT2is can normalize proximal reabsorption via tubular glomerular feedback, which should have particular effects on glomerular hemodynamics, eliminate diabetic hyperfiltration, and improve hard renal end points.…”
Section: Discussionmentioning
confidence: 99%